Inovasi Media Pembelajaran Berbasis Digital di Madrasah Ibtidaiyah - Salsabilah, Nadifa; Khairiah, Wapiatul (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to explore the application of digital-based learning media innovations in Islamic Religious Education at Ali Imran Madrasah Ibtidaiyah, as well as the challenges faced in its implementation. Based on the results of the study, various types of digital media such as educational videos, interactive applications, online platforms, and social media were used to increase student engagement in Islamic education. The results indicate that the use of digital media can enrich students' learning experiences, make learning more interactive and engaging, and improve students' understanding of Islamic teachings. However, the main challenges faced include limited technological infrastructure, such as devices and unstable internet connections, as well as challenges in changing the mindset of teachers and students who are accustomed to conventional methods. This study contributes to the development of digital-based Islamic education, particularly at the Madrasah Ibtidaiyah level, and provides recommendations for curriculum and policy development that are more adaptive to technology in religious education.